Relationships between dyadic coping, marital adjustment, and post-traumatic growth in patients with maintenance hemodialysis patients and their spouses - Zhang, Qi; Cao, Heng (Frontiers in Psychology, 2024)
Aim: To measure the relationships between dyadic coping, marital adjustment, and post-traumatic growth in patients with maintenance hemodialysis and their spouses. Background: Post-traumatic growth is common in patients facing maintenance hemodialysis. However, studies tend to focus on these patients as individuals rather than as part of a couple. Dyadic coping in a couple is important for their marital adjustment; however, little is known about how a couple's dyadic coping influences their marital adjustment and impacts their posttraumatic growth. Design: Cross-sectional study. Methods: A questionnaire survey was conducted among patients receiving maintenance hemodialysis and their spouses. Patients were recruited between December 2021 and October 2022 using convenience sampling from the blood purification centers of two first-class tertiary hospitals. A total of 230 couples (460 individuals) of patients receiving maintenance hemodialysis and their spouses were enrolled. A general condition questionnaire, the dyadic coping scale, and the Locke-Wallace marital adjustment scale were used for assessments and data entry and analysis were performed using EpiData 3.1, SPSS 25.0, and Mplus 8.4. Results: The dyadic coping of patients receiving maintenance hemodialysis was positively correlated with both marital adjustment and posttraumatic growth, as was the dyadic coping of their spouses. The marital adjustment of both patients and their spouses was found to partially mediate the association between dyadic coping and posttraumatic growth. Conclusion: Subject-mediated effects between the levels of dyadic coping, marital adjustment, and posttraumatic growth were established for both patients receiving maintenance hemodialysis and their spouses, and it was found that the marital adjustment in both showed varying degrees of mediation in the relationship between their dyadic coping and posttraumatic growth. Impact: The findings of the study suggest that attention should be given to promoting dyadic coping behaviors in patients receiving maintenance hemodialysis and their spouses. It is recommended that nurses offer both education and support to couples to promote dyadic coping.